The Effect of the LSLC-Based Guided Discovery Learning Model on Chemical Equilibrium Material on Student Learning Outcomes at SMA Negeri 14 Padang - Dita Yumarni Lase; Andromeda Andromeda (Universitas Negeri Padang, 2023)
Chemistry is a branch of natural science that is closely related to everyday life. Until now, it is mandatory to learn at the high school level is chemistry subject matter of chemical equilibrium. Chemistry lessons at this time tend not to be of interest to students because they are considered difficult. Based on data from interviews with several chemistry teachers at SMA 14 Padang, the material for chemical equilibrium was still difficult for students to understand, where learning at school was still teacher-centered. The solution is to apply the LSLC-based GDL model to encourage active students and improve quality and improve the course of a learning process. this type of research is quasi-experimental. the results of the research data are normally distributed and homogeneous, so the hypothesis test that is carried out is the t-test with 0.03 < 0.05. That is, the learning outcomes with chemical equilibrium material for students who were given treatment using the LSLC-based GDL model were higher than the learning outcomes of students who applied the GDL model without LSLC.